Fibrinolysis and Inflammation in Venous Thrombus Resolution - Mukhopadhyay, Subhradip; Johnson, Tierra A.; Duru, Nadire; Buzza, Marguerite S.; Pawar, Nisha R.; Sarkar, Rajabrata; Antalis, Toni M. (Frontiers in Immunology, 2019)
Clinical observations and accumulating laboratory evidence support a complex interplay between coagulation, inflammation, innate immunity and fibrinolysis in venous thromboembolism (VTE). VTE, which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), and the subsequent complications of post-thrombotic syndrome (PTS), are significant causes of morbidity and mortality in patients. Clinical risk factors for VTE include cancer, major trauma, surgery, sepsis, inflammatory bowel disease, paralysis, prolonged periods of immobility and aging. Abnormalities in venous blood flow or stasis initiates the activation of endothelial cells, and in concert with platelets, neutrophils and monocytes, propagates VTE in an intact vein. In addition, inflammatory cells play crucial roles in thrombus recanalization and restoration of blood flow via fibrinolysis and vascular remodeling. Faster resolution of the thrombus is key for improved disease prognosis. While in the clinical setting, anticoagulation therapy is successful in preventing propagation of venous thrombi, current therapies are not designed to inhibit inflammation, which can lead to the development of PTS. Animal models of DVT have provided many insights into the molecular and cellular mechanisms involved in the formation, propagation and resolution of venous thrombi as well as the roles of key components of the fibrinolytic system in these processes. Here, we review the recent advances in our understanding of fibrinolysis and inflammation in the resolution of VTE.